1989
DOI: 10.3133/ofr89260
|View full text |Cite
|
Sign up to set email alerts
|

Soil water and vegetation responses to precipitation and changes in depth to ground water in Owens Valley, California

Abstract: Gl Introduction Gl Purpose and scope G2 Background G2 Description of study area G3 Plant communities G3 Study design G5 Methods G9 Evaluation of drawdown G10 Site K G10 Site D G12 Site H G12 Site B G12 Soil water responses G12 Site K G15 Site D GL7 Site H G19 Site B G20 Vegetation responses G20 Vegetative cover G20 Response to precipitation G21 Response to changes in depth to ground water G24 Xylem pressure potential G25 Seasonal variation G28 Variation in predawn xylem pressure potential with changes in soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…Most studies of species distribution in the region have focused almost exclusively on the role of water availability in influencing the abundance of shrubs versus grasses (Elmore et al 2003(Elmore et al , 2006Griepentrog and Groeneveld 1981;Groeneveld and Or 1994;Groeneveld et al 1994;Naumburg et al 2005;Sorenson et al 1991). However, within a given watertable depth, community composition can be extremely variable, suggesting that other factors such as soil nutrients may play a critical role in plant function and distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of species distribution in the region have focused almost exclusively on the role of water availability in influencing the abundance of shrubs versus grasses (Elmore et al 2003(Elmore et al , 2006Griepentrog and Groeneveld 1981;Groeneveld and Or 1994;Groeneveld et al 1994;Naumburg et al 2005;Sorenson et al 1991). However, within a given watertable depth, community composition can be extremely variable, suggesting that other factors such as soil nutrients may play a critical role in plant function and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving Great Basin shrub species, the deep rooted Ericameria nauseosa (formerly Chrysothamnus nauseosus) was the only species to have an increased growth response to a summer precipitation event (Snyder et al 2004). Studies within Owens Valley have documented interannual variability in plant productivity and cover coinciding with interannual variability in precipitation patterns, even when plants have adequate access to groundwater Sorenson et al 1991). While these results have not been explicitly linked to N availability, they suggest that there may be an ecologically important relationship between shallow soil water, soil N availability, and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…water loss through ET approaches precipitation rates). However, in basins that have a shallow and reliable groundwater source, ET and plant growth will not be constrained by limitations associated with low precipitation; here, ET rates may exceed precipitation rates because plants (facultative and obligate phreatophytes) are able to access the groundwater (Meinzer, 1927;Sorenson et al, 1991;Scott et al, 2004;Elmore et al, 2006;Butler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Use of groundwater by phreatophytes is highest during the driest season of the year when alternative water sources become depleted and transpirational demand is highest. It is also suggested that phreatophytes are susceptible to the rate as well as season of drawdown (Mahoney and Rood 1992;Stromberg and Patten 1992;Tyree et al 1994;Scott et al 1999Scott et al , 2000Groom et al 2000;Shatfroth et al 2000;Horton et al 2001;Eamus et al 2006a) by having a higher rate of water-table decline than fine-root elongation rate, and/or lowering the water table during a time other than the root growth season (Sorenson et al 1991). Low magnitude and rates of change in groundwater levels as opposed to rapid drawdown, may allow intra-and inter-generational adaptation and persistence of phreatophytes (Scott et al 1999;Shatfroth et al 2000).…”
Section: Groundwater-dependent Ecosystem Management: Current Issuesmentioning
confidence: 99%